PENCIPTAAN TARI INS SPESIAL BERSAMA ANAK TUNAGRAHITA DI SLB A YKAB SURAKARTA - Dwi Mahendra; Jonet Sri Kuncoro (Institut Seni Indonesia Surakarta, 2021)
The journal Penciptaan Tari Ins Spesial Bersama Anak Penyandang Tunagrahita di SLB A YKAB Surakarta '' discusses one form of storytelling group dance with the theme of children with intellectual disabilities who want to show that they have dreams or hopes in the future. will be packaged in a non-story group choreography, compiled by Dwi Mahendra in 2019. This research is intended to describe the form of performance of the Special Ins dance and the creation of the Special Ins dance. The research method used is a qualitative research method using descriptive analytic. In this study using the reactive participation approach from Jonet Sri Kuncoro. Describing the creation of Special Ins Dance using Rhodes's creativity theory quoted by Utami Munandar in compiling Special Ins Dance, in describing the form of Special Ins Dance performances using the theory of Sumandiyo Hadi to elaborate on its elements. The results obtained in this study in the form of a description of the creation of Special Ins Dance prepared by Dwi Mahendra as well as a form of performance consisting of dance moves, dance halls, dance accompaniment or music, dance titles, dance themes, dance types, presentation modes, number of dancers and types dance genitals, makeup and costumes, lighting, and dance properties.Keywords: Ins Special Dance, form, process.